Association of initial assessment variables and mortality in severe pediatric traumatic brain injury - Eric A Sribnick; Kelli N Patterson; Rajan K Thakkar; Katherine C Bergus; Lindsey Asti; Josh Bricker; Tariku J Beyene; Lauren N Schulz; Dana M Schwartz (BMJ Publishing Group, 2024)
Background Predictive scales have been used to prognosticate long-term outcomes of traumatic brain injury (TBI), but gaps remain in predicting mortality using initial trauma resuscitation data. We sought to evaluate the association of clinical variables collected during the initial resuscitation of intubated pediatric severe patients with TBI with in-hospital mortality.Methods Intubated pediatric trauma patients <18 years with severe TBI (Glasgow coma scale (GCS) score ≤8) from January 2011 to December 2020 were included. Associations between initial trauma resuscitation variables (temperature, pulse, mean arterial blood pressure, GCS score, hemoglobin, international normalized ratio (INR), platelet count, oxygen saturation, end tidal carbon dioxide, blood glucose and pupillary response) and mortality were evaluated with multivariable logistic regression.Results Among 314 patients, median age was 5.5 years (interquartile range (IQR): 2.2-12.8), GCS score was 3 (IQR: 3-6), Head Abbreviated Injury Score (hAIS) was 4 (IQR: 3-5), and most had a severe (25-49) Injury Severity Score (ISS) (48.7%, 153/314). Overall mortality was 26.8%. GCS score, hAIS, ISS, INR, platelet count, and blood glucose were associated with in-hospital mortality (all p<0.05). As age and GCS score increased, the odds of mortality decreased. Each 1-point increase in GCS score was associated with a 35% decrease in odds of mortality. As hAIS, INR, and blood glucose increased, the odds of mortality increased. With each 1.0 unit increase in INR, the odds of mortality increased by 1427%.Conclusions Pediatric patients with severe TBI are at substantial risk for in-hospital mortality. Studies are needed to examine whether earlier interventions targeting specific parameters of INR and blood glucose impact mortality.